The Existence of The Reversal Burden of Proof of Corruption Criminal Acts in Investigations by the Police - Sumaryanto, A. Djoko; Kunarso, Kunarso; Saputra, Yoanes Ryan; Oktaviano, Gregorius; Paulus, James Junior (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
Law enforcement against corruption cases has always received special attention from the government, especially with the application of reversal of the burden of proof (omkering van het bewisjlast) as mandated by Article 37 of the Corruption Eradication Law (Law 31/1999 jo Law 20/2001). Investigation of corruption cases is the spearhead of law enforcement in eradicating corruption in Indonesia, but to find out law enforcement at the investigation level by applying reversal of the burden of corruption still needs to be examined more deeply. To find out and understand the implementation of investigations using reversal of the burden of proof, normative legal methods are carried out with field research, namely by using a statutory approach, case approach and concept approach, by examining legal materials obtained through literature review and online, as well as by conducting several interviews with investigators, then analysed using the deduction method and explained using descriptive analysis, to obtain comprehensive study results. From the discussion, an analysis of the existence of the reversal of the burden of proof in the investigation of corruption cases in the police is obtained that the information on the assets owned by the suspect is not all true, after obtaining information from witnesses who have been involved in corruption against the suspect, and only confiscation of property that is the result of corruption is carried out, then proven by the suspect at a court hearing (reversal of the burden of proof / Omkering van het Bewishlasj).